STRUCTURAL AND PALEOGEOGRAPHIC REORGANIZATIONS IN EARTH HISTORY - Sobol'yev V.O. (My University, 1988)
Many authors have substantiated the synchronous expansion or contraction of sea basins in different parts of the world. On the other hand, it is well known that transgressions and regressions were contemporaneous in isolated parts of the same continents, so the single global trend of their evolution cannot be proved in certain cases. We illustrate this by several examples from such a comparatively thoroughly studied region as Eurasia. The data show that expansion or contraction of areas of marine or continental sedimentation in some regions of a continent coincided with the opposite paleo-geographic phenomena in others. Such phenomenon should be interpreted not as a random local coincidence of paleogeographic inversions, but as an extensively manifested process that occurred at times of certain structural reorganizations in earth history.